PENGARUH RENDAM AIR HANGAT TERHADAP KRAM KAKI IBU HAMIL. DI PMB VITRI SUZANTI PALEMBANG - Anggeni, Untari; Septriana; Marini, Yoan (LPPM STIKes Mitra Adiguna, 2025)
Mindell et al. first trimester the percentage of leg cramps was 20.9%; the percentage increased ranging from 24.6% to 42.1% in the second trimester 47.8% to 50.0% in the third trimester. (Abandeh et al., 2024). Warm water immersion is the application of heat to the body to reduce acute or chronic pain. This study aims to determine whether warm water immersion affects leg cramps in pregnant women at PMB Vitri Suzanti in 2024. This research method is quantitative pre-experimental with pre-post test one group as the research design. All pregnant women who visited PMB Vitri Suzanti Palembang were the population of this study with a total of 48 respondents and managed to get a sample of 20 respondents who met the inclusion criteria. Based on the results of statistical analysis using the Wilcoxon test, P = 0.001 <0.05 was obtained, Therefore, Ho was turned down, Ha was accepted, however, suggesting that the level of pain before and after soaking in warm water was different after being given 5 days of care so that soaking in warm water had an effect on leg cramps in pregnant women at PMB Vitri Suzanti Palembang 2024. Suggestions are expected that health educators can educate and promote to pregnant women about the importance of carrying out non-pharmacological treatment, namely soaking in water to eliminate the discomfort of leg cramps during pregnancy.